Exploring Linkages of the Emergent Economies under a European Sovereign Debt Crisis Context - Ferreira, N. B.; Manuela Oliveira (8th Annual American Business Research Conference, 2016)
The aim of the study is to identify the international economic linkages between European emergent countries and different economies under the European sovereign debt crisis from the eighties till 2015. More precisely, Portugal, Ireland and Greece economies are compared with more economically sustainable countries (such France, Germany, United Kingdom, Norway and Denmark). Switzerland, China and United States were also included to evaluate the European Union external impacts. To examine the increasing macro-financial linkages and their interactions were included in a Global VAR model, credit variables to analyze international transmission of the emerging Euro area along with US, China and Switzerland credit and aggregate demand shocks. Another relevant variables such as consumer spending, consumer confidence, consumer price inflation and employment were also included. The model was set up with quarterly data for a sample of 11 countries and three endogenous variables: Real GDP, stock price indices, and long term interest rates. The results showed that the emerging Portuguese economy in the Euro region revealed to be quite different from other European markets under the sovereign debt.